Entrepreneur Orientation and Social Capital As A Key To Developing Dynamic Capability: A Conceptual Framework - Annuridya Rosyidta Pratiwi Octasylva; Yuliati, Lilik Noor; Hartoyo; Soehadi, Agus W (School of Business, IPB University (SB-IPB), 2023)
Various economic problems can be solved with good entrepreneurship. SMEs are part of entrepreneurship that plays an essential role in the economy, including reducing unemployment and improving a country's economy. Environmental conditions that are VUCA (Volatility, Uncertainty, Complexity, Ambiguity) make SMEs have obstacles such as lack of competence, capacity, knowledge and skills of SME actors to adapt in running a business. The ability of SMEs to be able to continue to run their business makes SMEs must have dynamic capabilities that come from internal and external SMEs. Therefore, the purpose of this paper is to review the relevant literature in determining the theories that can shape the dynamic capabilities of SMEs. Based on a literature review, this research generated the result that entrepreneurial orientation (internal) and social capital (external) is critical in developing SMEs' dynamic capability. Keywords: dynamic capability, entrepreneur orientation, literature review, small medium entrepreneur, social capital